Análisis e interpretación a los estados financieros De Lavanderías Loja cía. Ltda., periodo 2009-2010-2011 - Medina Mocha, Adriana Yissel (2014)
The present thesis work is denominated "Analysis and Interpretation to the Financial States of Laundries Loja Co. Ltda., period 2009-2010-2011. ", the same one that was carried out to give execution to the prerequisites to the obtaining of the Title of Ingenerate in Accounting and Audit, CPA., in the National University of Loja, according to the Regulation of effective Academic Régime. The realization of the same one allows determining that the system of administrative and financial administration that maintains the company is the most appropriate. Execution has been given to the objectives layouts inside this investigation work, carrying out the vertical, horizontal analysis, graph, applying financial indexes and the respective report with the results that allow to determine the real position of the company, this whole process of the financial analysis allowed to toast alternative of solution in order to of strengthening the administration carried out by its administrators. Among the main results, product of the investigation work, when analyzing the different bills of the States Financiers, is evidenced that the company maintains a high level of indebtedness, due to long term loans shareholders and a high percentage in administration expenses, affecting this way to the profitability of the company, it is as well as in the main conclusion he/she settles down that he/she has been carried out the financial analysis that shows that the company has problems of profitability that affect its economic and financial stability, likewise it is recommended that the company should adopt tools of financial analysis at least once a year, to know its financial situation and to take the necessary correctives.